2012
DOI: 10.5935/1678-9741.20120039
|View full text |Cite
|
Sign up to set email alerts
|

Six-minute walk test as a tool for assessing the quality of life in patients undergoing coronary artery bypass grafting surgery

Abstract: Teste de caminhada de seis minutos como ferramenta para avaliar a qualidade de vida em pacientes submetidos à cirurgia de revascularização miocárdicaSix-minute walk test as a tool for assessing the quality of life in patients undergoing coronary artery bypass grafting surgery Abstract Objective: Evaluate the quality of life in patients undergoing myocardial revascularization using the sixminute walk test.Methods: This is a prospective observational study with patients undergoing CABG. We recorded the following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 23 publications
0
5
0
2
Order By: Relevance
“…Peripheral muscle force (PMS) can be regarded as a predictor of overall muscular strength, and is associated with functional and nutritional presentation of the patient [ 12 , 13 ] . Nevertheless, the PMS has been little explored in the literature, especially in the context of complications from surgery, the reason why the study was proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral muscle force (PMS) can be regarded as a predictor of overall muscular strength, and is associated with functional and nutritional presentation of the patient [ 12 , 13 ] . Nevertheless, the PMS has been little explored in the literature, especially in the context of complications from surgery, the reason why the study was proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Baptista et al [24] reported that CABG surgery improved the HRQoL scores in all patients; however, the improvement was greater in patients who walked less than 350 meters preoperatively. In our study, we did not find any difference in the HRQoL scores between the groups.…”
Section: Discussionmentioning
confidence: 96%
“…298 Aunque existen estudios que valoran la influencia del 6WT en pacientes con enfermedad coronaria y en el postoperatorio de cirugía cardíaca, [299][300][301][302][303][304] no se han encontrado publicaciones que relacionen dicho parámetro con la necesidad de CEC durante el TP. Así mismo, tampoco se han encontrado publicaciones que relacionen la PaCO 2 y el FVC como factores de riesgo para la necesidad de CEC durante el TP.…”
Section: Factores De Riesgo De Cecunclassified